1999
DOI: 10.1677/joe.0.1620443
|View full text |Cite
|
Sign up to set email alerts
|

Culture of prostate epithelial cells of the rhesus monkey on extracellular matrix substrate: influence of steroids and insulin-like growth factors

Abstract: Rhesus monkey prostate epithelial cells from the cranial lobe were isolated and cultured in flasks coated either with collagen IV or laminin. The effects of stromal cell medium, androgens and growth factors on cell number, thymidine incorporation and secretory activity were assessed.The results indicate that dihydrotestosterone (DHT) and androstenedione have stimulatory influences on cell proliferation and secretion in coated flasks. DHT was more effective in increasing cell number but the induction of secreto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…Insulin or epidermal growth factor (possibly produced locally by the stromal component of the prostate) together with testosterone may contribute to the regulation of prostate cell proliferation, acting through a paracrine stromal/acinar loop (Berthon et al, 1997;Culing et al, 1995Culing et al, , 1996Griffiths et al, 1997;Russell et al, 1998;Sherwood et al, 1998;Udayakumar et al, 1999). Thus, it is important to understand how post receptor pathways, activated through different receptors, interact to control proliferation and differentiation of prostate cells.…”
Section: P Rostate Cancer Is the Most Common Cancer Inmentioning
confidence: 99%
“…Insulin or epidermal growth factor (possibly produced locally by the stromal component of the prostate) together with testosterone may contribute to the regulation of prostate cell proliferation, acting through a paracrine stromal/acinar loop (Berthon et al, 1997;Culing et al, 1995Culing et al, , 1996Griffiths et al, 1997;Russell et al, 1998;Sherwood et al, 1998;Udayakumar et al, 1999). Thus, it is important to understand how post receptor pathways, activated through different receptors, interact to control proliferation and differentiation of prostate cells.…”
Section: P Rostate Cancer Is the Most Common Cancer Inmentioning
confidence: 99%
“…In addition, estrogens enhanced synthesis of epidermal growth factor (EGF) and insulin like growth factor-1 (IGF-1) via an ER-mediated pathway to excite prostatic enlargement as demonstrated in organ culture of rat fetal prostate [ 108 ]. In line with these observations, these growth factors can stimulate growth of prostatic epithelium [ 109 , 110 ]. Administration of EGF or bFGF orthotopically in ventral prostates of adult rats increased the prostate size with enhanced growth of prostatic epithelium [ 109 ].…”
Section: Estrogen Receptors (Ers) and Estrogenic Actions In Normalmentioning
confidence: 78%
“…It has been suggested that either a limited but sustained growth promotion or, alternatively, ineffective restraint of cell proliferation, indicating alteration in the capacity of epithelial cells to respond to transforming growth factor ␤ (TGF␤), induced an imbalance, which resulted in the development of epithelial hyperplasia and nodular growth (Griffiths, 1996). Other members of the growth factor family that have a mitogenic effect on prostate epithelial cells in culture include fibroblastlike growth factor (Kabalin et al, 1989;Udayakumar et al, 1999), keratinocyte growth factor (Yan et al, 1992), and insulin-like growth factor (Cohen et al, 1994;Udayakumar et al, 1999). It is likely that overexpression of these mitogenic factors along with underexpression of TGF␤ under androgenic and estrogenic regulation may cause the imbalance that results in BPH.…”
Section: Discussionmentioning
confidence: 99%